Identification of a receptor for the sex pheromone of the vine mealybug, Planococcus ficus - Jacob A. Corcoran; Walter F. Mahaffee (Current Research in Insect Science, 2024)
The vine mealybug, Planococcus ficus, is a significant pest of vineyards in all major grape growing regions of the world. This pest causes significant aesthetic damage to berry clusters through its feeding behavior and secretion of ''honeydew'', which leads to significant decreases in crop marketability. More importantly, the vine mealybug is a vector of several grapevine viruses which are the causal agent of grapevine leafroll disease, one of the most destructive and economically devastating diseases of the grape industry worldwide. As there is no cure for grapevine leafroll disease, the only control measures available to reduce its spread are to remove infected vines whilst simultaneously controlling mealybug populations. Using transcriptomic libraries prepared from male and female mealybugs and a draft genome, we identified and evaluated expression levels of members of the odorant receptor gene family. Interestingly, of the 50 odorant receptors identified from these P. ficus genetic resources, only 23 were found to be expressed in females, suggesting this flightless life stage has a decreased reliance on the olfactory system. In contrast, 46 odorant receptors were found to be expressed in the alate male life stage. Heterologous expression of eight of these receptors, along with the obligate co-receptor, Orco, in HEK293 cells allowed for the identification of two receptors that respond to lavandulyl senecioate, the sole constituent of the sex pheromone used by this species. Interestingly, one of these receptors, PficOR8, also responded to the sex pheromone used by the Japanese mealybug, Planococcus kraunhiae. The data presented here represent the first report of odorant receptor gene family expression levels, as well as the identification of the first sex pheromone receptor, in soft-scale insects. The identification of a receptor for the vine mealybug sex pheromone will allow for the development of novel, species-specific pest control tools and monitoring devices.